2016
DOI: 10.1021/acs.jpcc.6b06564
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Ion Disorder and Conduction Mechanism in LiCe(BH4)3Cl

Abstract: We investigate the diffusion mechanism of Li ions in LiCe(BH 4 ) 3 Cl, which exhibits fast Li ion conduction. It was previously shown that eight Li ions partially occupy the 12d Wyckoff sites in the I4̅ 3m structure and the Li ion diffusion takes place via jumping through the three-dimensional network of the 12d sites. In this study, we employ firstprinciples nudged elastic band simulation to elucidate the diffusion mechanism and discover that the Li ion does not directly jump to the neighboring 12d site, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Recent interest in utilizing LiBH 4 as a solid-state electrolyte was established through the work of Orimo [4], who demonstrated that the ionic conductivity of lithium can be greater than 1 mS/cm at temperatures above the orthorhombic to hexagonal phase transition that occurs at 380 K [5]. This work has been expanded to achieve high conductivity in LiBH 4 based solid electrolytes through the addition of Li halide salts [6][7][8], nanoconfinement [9][10][11][12], nanoionic destabilization [13,14], ion substitution [15][16][17][18][19][20][21], and eutectic formation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest in utilizing LiBH 4 as a solid-state electrolyte was established through the work of Orimo [4], who demonstrated that the ionic conductivity of lithium can be greater than 1 mS/cm at temperatures above the orthorhombic to hexagonal phase transition that occurs at 380 K [5]. This work has been expanded to achieve high conductivity in LiBH 4 based solid electrolytes through the addition of Li halide salts [6][7][8], nanoconfinement [9][10][11][12], nanoionic destabilization [13,14], ion substitution [15][16][17][18][19][20][21], and eutectic formation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of ionic conduction mechanisms in borohydrides showed that it is not only vacancy-dependent but also based on the "paddle-wheel" mechanism [47][48][49] wherein the high rotational mobility of the (M y X n ) δ− units promotes the ionic conductivity and lowers the activation energy [50,51]. This concept inspired investigating boron clusters (closo-borates)-based salts as electrolytes.…”
Section: Towards Achieving High LI + Na + Mobilities: Closo-boratesmentioning
confidence: 99%
“…Investigations of ionic conduction mechanism in borohydrides showed that its not only vacancy-dependent but also based on the "paddle-wheel" mechanism. [47][48][49] wherein the high rotational mobility of the [MyXn] δ-units promotes the ionic conductivity and lowers the activation energy. [50][51] This concept inspired investigating boron clusters-based salts as electrolytes.…”
Section: Towards Achieving High Solid State LI + Na + Mobilities: Cmentioning
confidence: 99%